Sound Intensity Mapping of an Engine Dynamometer - M. S. M., Sani; M. M., Rahman; M. Z., Baharom; I., Zaman (Universiti Malaysia Pahang, 2015)
This paper presents an investigation of the noise source identification (NSI) in a diesel engine at different engine speeds. An experiment was conducted utilizing an eddy current dynamometer with a sound intensity mapping method for the engine speed range of 1500 rpm to 2000 rpm. The noise source of the flywheel cover and manifold are presented. It can be observed that the critical cut-off frequency is 1250 Hz. The sound level powers are within the range of 86.42 dB to 96.34 dB in varying engine speeds. Further, the noise level is found to be increasing with engine speed. Another main source of vibration is engine mounting, which has a significant effect on noise level due to the engine’s structural vibration transfer and noise radiation behavior with respect to the excitation mechanism. The noise power level for mounting is within the range of 77.17 dB to 89.96 dB for an engine speed of 1500 rpm to 2000 rpm. This method can be applied on-site rather than in an anechoic chamber as long as the background noises are stationary. The project delivers a reliable input for the engineering practice to reduce engine noise level.